IS/IT Strategic Planning At STMIK Dian Cipta Cendikia Kotabumi - Ferly Ardhy (STMIK Pringsewu Lampung, 2018)
The purpose of this research is to know how big function of business environment and IS / IT that exist in STMIK Dian Cipta Cendikia Kotabumi. In this research will pass several stages and methods applied in this research are questionnaires, interviews and the use of Strategic Planning IS / IT (Ward & Peppard). From the results of this study will get output in the form of long-term strategy especially in the field of IS / IT, namely what applications will be needed to support every business process and supporting technology needs in the environment STMIK Dian Cipta Cendikia Kotabumi in the future. From the results of this study can be a reference by the development team in order to implement the Development of IT / IT to support existing business processes on STMIK Dian Ciptta Cendikia.